Ferritin Levels and Their Association With Regional Brain Volumes in Tourette's Syndrome - Gorman, Daniel A. (2006)
OBJECTIVE: A previous small study showed lower serum ferritin levels in subjects with Tourette's syndrome than in healthy subjects. The authors measured peripheral iron indices in a large group of Tourette's syndrome and comparison subjects and explored associations of ferritin levels with regional brain volumes. METHOD: Ferritin was measured in 107 children and adults (63 Tourette's syndrome, 44 comparison); serum iron was measured in 73 (41 Tourette's syndrome, 32 comparison). Magnetic resonance imaging scans were used to measure volumes of the basal ganglia and cortical gray matter. RESULTS: Ferritin and serum iron were significantly lower in the Tourette's syndrome subjects, although still within the normal range. No association was found between tic severity and either iron index. In the Tourette's syndrome subjects, ferritin did not correlate significantly with caudate volume but did correlate positively with putamen volume. In the comparison subjects, ferritin correlated inversely with caudate volume but did not correlate significantly with putamen volume. Irrespective of diagnosis, ferritin correlated positively with volumes of the sensorimotor, midtemporal, and subgenual cortices. CONCLUSIONS: The lower peripheral ferritin and iron levels in persons with Tourette's syndrome are consistent with findings in other movement disorders and suggest that lower iron availability may have a causal role in the pathophysiology of tic disorders. Lower iron stores may contribute to hypoplasia of the caudate and putamen, increasing vulnerability to developing tics or to having more severe tics. Lower iron stores may also contribute to smaller cortical volumes and consequently to reduced inhibitory control of tics.